2022
DOI: 10.1186/s12960-022-00733-0
|View full text |Cite|
|
Sign up to set email alerts
|

WHO competency framework for health authorities and institutions to manage infodemics: its development and features

Abstract: Background In April 2020, the World Health Organization (WHO) Information Network for Epidemics produced an agenda for managing the COVID-19 infodemic. “Infodemic” refers to the overabundance of information—including mis- and disinformation. In this agenda it was pointed out the need to create a competency framework for infodemic management (IM). This framework was released by WHO on 20th September 2021. This paper presents the WHO framework for IM by highlighting the different investigative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 35 publications
0
30
0
1
Order By: Relevance
“…According to Norman and Skinner ( 21 ), e-health literacy, or what is often also referred to as digital health literacy, is a complex construct that consists of six types of literacy, namely: ( 1 ) computer or digital literacy, which refers to skills related to using a computer and the Internet; ( 2 ) information literacy, which includes the competences of searching, evaluating and using retrieved information; ( 3 ) media literacy, which pertains to the skills and knowledge required to interpret various audio and visual forms of resources and create meaning out of their content; ( 4 ) traditional literacy, which refers to the basic skills of writing, reading, calculating, understanding and interpreting information in a given context; ( 5 ) science literacy, which consists of competences of knowing basic scientific concepts and reasoning, which helps individuals to understand, evaluate, and give meaning to basic scientific facts; and ( 6 ) health literacy.…”
Section: Context Specific Conceptualizations Of Health Literacy and I...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Norman and Skinner ( 21 ), e-health literacy, or what is often also referred to as digital health literacy, is a complex construct that consists of six types of literacy, namely: ( 1 ) computer or digital literacy, which refers to skills related to using a computer and the Internet; ( 2 ) information literacy, which includes the competences of searching, evaluating and using retrieved information; ( 3 ) media literacy, which pertains to the skills and knowledge required to interpret various audio and visual forms of resources and create meaning out of their content; ( 4 ) traditional literacy, which refers to the basic skills of writing, reading, calculating, understanding and interpreting information in a given context; ( 5 ) science literacy, which consists of competences of knowing basic scientific concepts and reasoning, which helps individuals to understand, evaluate, and give meaning to basic scientific facts; and ( 6 ) health literacy.…”
Section: Context Specific Conceptualizations Of Health Literacy and I...mentioning
confidence: 99%
“…Accordingly, it is not surprising that increasing health literacy is one of the WHO’s preoccupations ( 5 ). Health literacy plays a crucial role also in current infodemic management plans ( 6 ) intended to protect people from an increasing overabundance of (in)valid information related to specific health topics, conditions or diseases in the physical and digital environment ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the author name of Elisabeth Wilhelm.…”
Section: Correction To: Human Resources For Health (2022) 20:35 10118...mentioning
confidence: 99%
“…Malnutrition can exacerbate the effects of chronic disease management and lead to an increased risk of complications during treatment, increased mortality and poorer quality of life for patients during and after treatment ( 6 ). All these negative consequences of malnutrition also have a negative financial impact on the healthcare system, as the treatment of malnourished patients increases the number of visits to the primary care physician or home visits and directly correlates with longer hospital stays and increased hospital readmissions due to complications ( 7 ).…”
Section: Introductionmentioning
confidence: 99%